Peningkatan Strategi Pemasaran Online Produksi Jamu Tradisional - Yani, Yepita Ghufiromah; Wafa, Zaenal (Journal of Social Responsibility Projects by Higher Education Forum, 2024)
This study aims to improve the online marketing strategy of traditional herbal medicine products from "Omah Jamu Tradisional Watu" using the AIDA (Attention, Interest, Desire, Action) concept on the Instagram platform. The main issues identified were low product visibility and minimal customer engagement. The implemented solutions included creating attractive visual content, utilizing paid advertising campaigns, and active interaction through Instagram Stories and Live features. Publishing customer testimonials and collaborating with influencers effectively built trust and purchase interest, while clear Call-to-Action (CTA) implementation simplified the purchasing process. The results showed significant increases in followers, audience engagement, and product sales. In conclusion, the AIDA-based marketing strategy on Instagram proved effective in enhancing visibility and sales of traditional herbal medicine products. The study recommends consistency in producing high-quality content and leveraging data analytics for continuous optimization.